The Relation Between Pedagogical Approaches in Music Education and Students' Performance Anxiety - Balija Susić, Blaženka (Revija za elementarno izobraževanje, 2018)
Performance anxiety is a significant problem in general education, as well as in music education. Therefore, the purpose of this study is to determine whether the Functional Music Pedagogy (FMP) approach has asignificant effect on music performance anxiety in children. The neglect of improvisation as a basic methodological tool in FMP instrumental practice could explain why the main effect of school type was not significant in this sample. The lack of Music Performance Anxiety differences between students who havelearned music through distinct pedagogical approaches can be interpreted as a result of the physiological and psychological developmental changes that arise on entering puberty as a consequence of hormonal changes and increased emotions during early adolescence.DOI: 10.18690/rei.11.2.143-157.2018COBISS-ID:
Keywords: Elly Bašić; functional music pedagogy; music education; music school with standard program; music performance anxiety